2007
DOI: 10.1074/jbc.m607871200
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the Activation of the Human Hyaluronan Synthase 2 Gene Promoter by Common Cofactors of the Transcription Factors Retinoic Acid Receptor and Nuclear Factor κB

Abstract: Hyaluronan (HA) is a polysaccharide of the vertebrate extracellular matrix, produced by three related HA synthases (HASs) that influence numerous physiological processes. We screened the first 2250 bp of the HAS2 promoter for transcription factor response elements (REs) in silico and found 1 cluster of 2 retinoic acid (RA) REs, 3 discrete NF-B factors, and 12 Sp1 REs. In parallel, we scanned nine overlapping promoter regions in HaCaT human immortalized keratinocytes using chromatin immunoprecipitation assays t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
(44 reference statements)
6
46
0
Order By: Relevance
“…Several functional REs on the HAS2 promoter have been verified previously (7,11,16). However, following 6-h treatments with mannose and glucosamine, no changes in the recruitment of CREB1, NF-B, and STAT3 were noted on the first 2250 bp of the promoter (data not shown), suggesting that the previously described signals related to G-protein-coupled receptors, inflammation or cell survival, and growth factors like EGF (7,11,16) are not part of the pathways that carry UDP-HexNAc information to HAS2 transcription.…”
Section: Mechanism Of Udp-hexnac Control Of Has2 Expressionto Explorementioning
confidence: 70%
See 4 more Smart Citations
“…Several functional REs on the HAS2 promoter have been verified previously (7,11,16). However, following 6-h treatments with mannose and glucosamine, no changes in the recruitment of CREB1, NF-B, and STAT3 were noted on the first 2250 bp of the promoter (data not shown), suggesting that the previously described signals related to G-protein-coupled receptors, inflammation or cell survival, and growth factors like EGF (7,11,16) are not part of the pathways that carry UDP-HexNAc information to HAS2 transcription.…”
Section: Mechanism Of Udp-hexnac Control Of Has2 Expressionto Explorementioning
confidence: 70%
“…Mannose and Glucosamine Regulate the Levels of HAS2 mRNA-Because the synthesis of hyaluronan showed an attenuated response to substrate supply, we measured the expression level of HAS2 mRNA, the dominant HAS isoenzyme in these cells (16). Quantitative RT-PCR indicated that enhanced HAS2 expression took place at 20 mM mannose already after 2 h, reached a 90% increase at 6 h, and decreased to 15% after 24 h (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations